A study of sibling rivalry in fifty pre-school children - Griffith, Carole Doreen (Department of Psychology, 2016)
An exploratory study of 50 pre-school children was carried out in an attempt to assess the influence on sibling rivalry of maternal attitudes, family composition and the child's perceptions of family relations. Maternal attitudes and the child's attitude towards parents were not related to sibling rivalry. Rivalry was significantly higher following displacement and at the closer spacings. The results were interpreted in terms of an interactional analysis of sibling rivalry.